Peranan Contagion Effect pada Krisis Mata Uang di Indonesia - Hadi Sutrisno; Muhammad Rusmin Nuryadin (Ecoplan, 2023)
This research was conducted in the period 1991(1)-2021(12), aiming to look at the contagion effect of the currency crisis in Indonesia. They were leading macroeconomic indicators as indicators/signals of impending or non-occurring problems. Determination of the currency crisis period based on EMPI (Exchange Market Pressure Index) by setting a threshold (threshold) at a specific value. Two models are used in this research: the Herrera-Garcia model and the Signal Analysis Model. The Herrera-Garcia model is based on the Composite Index generated from the Leading Indicator in detecting signals of impending crises by considering efficiency. The Signal Analysis model is used to analyze the impact of the contagion effect on currency crises, relying more on its accuracy than the Herrera-Garcia model. The results showed that the currency crisis that occurred in countries in the region impacted the currency crisis in Indonesia, where the crisis from one country had a Contagion Effect that differed in contribution from other countries.